PENERAPAN METODE PEMBELAJARAN OUTDOOR PADA SISWA UNTUK MATA PELAJARAN KOMUNIKASI DI SEKOLAH MENENGAH KESEHATAN - Rita Rena Pudyastuti (Poltekkes Kemenkes Maluku, 2019)
Learning outside the classroom (outdoor study) is an effort to create learning, to avoid boredom and perceptual learning only in class. The approach to learning outside the classroom uses several methods such as assignment, question and answer, and learning while doing or practicing with learning situations while playing. Students get bored quickly with conventional methods. This study aims to determine the effectiveness of pre and post test using the method of learning outdoor study on Communication subjects to increase the learning achievement of Nursing Health Department Vocational High School students totaling 80 students. The design of this study is Quasi Experiment research. Data collection methods that will be used in this study are pre test and post test questionnaires distributed to students of the Nursing Department, before and after the Communication teaching and learning process using outdoor teaching methods and conventional methods. To analyze data using paired T Test. The results obtained are that there is a significance between the pre test and post test of the learning outdoor method, which is 0.00. But the use of conventional methods is not significant with a result of 0.50. Keywords: Learning method, outdoor, conventional